KUALITAS PELAYANAN E-LIBRARY (PERPUSTAKAAN ELEKTRONIK) DI PERPPUSTAKAAN WILAYAH SOEMAN HS PROVINSI RIAU - Rahayu Suprianti; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research is a study to describe e-library services. the electronic (E-library) is a library that holds data those in the (writing), pictures, voices in the form of electronic files and distribute them using electronic protocol via computer networks. Based on observation, the problems that happened is the lack of attention for facility of the library completeness e-library and management of devices those are not optimal.The research is to determine and analyze service quality e-library (the library email) in the Soeman Hs Libarary in the Province of Riau and to determine and analyze the factors that affect the quality of e-library services (the library email) at the Soeman Hs library in the Province of Riau.The concept of the theory that used is the service has the Tangible, Reliability, Responsiveness, Assurance, and Empaty. This study is using the method of qualitative research with data collection is descriptive. In the collection of data the author uses of the interview techniques, observation, and documentation. The key informants as a source of information and analyze of data.The conclusion of the research the Soeman Hs library has good enough quality in served the community and in according with what is expectation by the visitors the library, and to complete the facilities and infrastructure, especially e-library is less to the amount of hardware that's available, you know the factors those affect the quality of service in the Soeman Hs library are the facilities and infrastructure those are not adequate and human resources (HR) who lacks educational background of the library is needed.Keywords : Service, E-Library